A History of Wine in America, Volume 1 : From the Beginnings to Prohibition - Pinney, Thomas (Book collections on Project MUSE., 2005)
Wine-making in the United States as it was carried out under Prohibition and then as it developed and spread to all fifty states after the repeal of Prohibition is described in this account of the American vintner's art as it has evolved into a successful enterprise.